1992
DOI: 10.1128/aem.58.1.359-364.1992
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Growth in the Cold: Evidence for an Enhanced Substrate Requirement

Abstract: Growth responses and biovolume changes for four facultatively psychrophilic bacterial isolates from Conception Bay, Newfoundland, and the Arctic Ocean were examined at temperatures from-1.5 to 35°C, with substrate concentrations of 0.15, 1.5, and 1,500 mg of proteose peptone-yeast extract per liter. For two cultures, growth in 0.1, 1.0, and 1,000 mg of proline per liter was also examined. At 10 to 15°C and above, growth rates showed no marked effect of substrate concentration, while at-1.5 and 0°C, there was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
2
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(61 citation statements)
references
References 34 publications
4
54
2
1
Order By: Relevance
“…Another explanation would be less e⁄cient coupling of electron transfer between substrate oxidation and sulfate reduction at low temperature. The latter assumption is in agreement with the observation that mesophilic marine bacteria have lower growth e⁄ciencies at low temperature [39]. With respect to SRR, the 28 ‡C culture was better adapted to intermediate temperatures (10^25 ‡C) than the 4 ‡C and 10 ‡C cultures.…”
Section: Discussionsupporting
confidence: 89%
“…Another explanation would be less e⁄cient coupling of electron transfer between substrate oxidation and sulfate reduction at low temperature. The latter assumption is in agreement with the observation that mesophilic marine bacteria have lower growth e⁄ciencies at low temperature [39]. With respect to SRR, the 28 ‡C culture was better adapted to intermediate temperatures (10^25 ‡C) than the 4 ‡C and 10 ‡C cultures.…”
Section: Discussionsupporting
confidence: 89%
“…manner to increased phytoplankton abundance, but the strength of the relationship may be weaker than that observed in temperate and tropical areas. The cause of the diminished activity of bacteria in high-latitude waters has been suggested to be an increased requirement for organic substrates at low temperatures [Wiebe et al, 1992], but the data presented here are inadequate to test this hypothesis. We can, however, draw inferences from an analysis of data on standing stocks.…”
Section: Discussionmentioning
confidence: 57%
“…The slopes of the regression lines for both data sets were positive and nearly identical, suggesting that the functional response in both the diatom-and flagellate-dominated areas was similar. Ducklow and Carlson [1992] suggested that a positive bacterial-chlorophyll relationship was indicative of resource limitation of bacteria, in keeping with the substrate limitation hypothesis of Wiebe et al [ 1992]. They also suggested that if the slope of the relationship was less than one, then at high phytoplankton and bacterial standing stocks the relationship potentially is impacted by grazing on bacteria.…”
Section: Discussionmentioning
confidence: 94%
“…Such virus-host co-occurring variability in temperature sensitivity, within the optimum range host growth, will enhance the temporal intraspecies diversity index. Temperature is a major regulatory factor for microbial growth (through the regulation of enzyme kinetics, molecular diffusion, and membrane transport) and therefore can be expected to affect viral life strategy and viral production (White et al, 1991;Wiebe et al, 1992). Indeed, prophage (uHSIC ) induction correlated to seasonal variations in temperature (from 15 to 30°C) in a eutrophic estuary was found to be a consequence of a twofold higher growth rate of the host (Listonella pelagia) at 28°C compared to 18°C Williamson et al, 2002;Williamson & Paul, 2006).…”
Section: Temperaturementioning
confidence: 99%